Using active noise-cancelling headphones in open-plan offices: No influence on cognitive performance but improvement of perceived privacy and acoustic environment - Mueller, Benjamin Johannes; Liebl, Andreas; Herget, Noemi; Kohler, Dorina; Leistner, Philip (Frontiers in Built Environment, 2022)
High speech intelligibility in open-plan offices and thus a high changing-state character of the acoustic environment have been found to negatively influence cognitive performance. This is often attributed to the so-called irrelevant speech effect (ISE). Office workers lately use active noise-cancelling (ANC) headphones to improve the acoustic situation by blocking unwanted sound. However, it is currently unknown if using ANC headphones in a noisy setting improves cognitive performance. Two studies were conducted to examine if ANC headphones improve cognitive performance and the subjective well-being of employees in an open-plan office. Cognitive performance was measured using a serial recall test. Subjective assessments were measured using a questionnaire. The participants were tested in silence, speech without headphones, speech with ANC headphones switched off and speech with ANC headphones switched on. No statistically significant differences were found between the conditions with ANC headphones switched on and off as well as without headphones for cognitive performance. However, ANC headphones statistically significantly improved subjective assessments such as perceived privacy and the assessment of the acoustic environment. The results provide a scientific basis for evaluating and planning the appropriate use of ANC headphones for concentration-intensive activities such as office work.